Influence of Family Financial Education and Socioeconomic Status on Financial Literacy with Well-Being as Mediator - Ayuninggar, Imaniar Lintang; Prayitno, Putra Hilmi; Wahjoedi, Wahjoedi; Inayati, Ro’ufah (Jurnal Pendidikan dan Pembelajaran Indonesia (JPPI), 2024)
This research investigates how family-based financial management education and parents' socioeconomic status impact financial literacy among grade XI students at MAN 2 Malang - Turen. Additionally, it explores the role of financial well-being as a mediating variable in the relationship between family financial education, parental socioeconomic status, and students' financial literacy. The study employs a quantitative approach, utilizing Structural Equation Modeling (SEM) based on Partial Least Square (PLS) for data analysis. A total of 110 grade XI students from MAN 2 Malang - Turen participated in this research. The findings indicate that family financial education significantly influences students' financial literacy. Conversely, while parents' socioeconomic status has a positive impact on financial literacy through financial well-being, this effect is not statistically significant. This outcome is attributed to economic disparities among students' families, challenging job conditions, and limited resources, which often prompt parents to migrate for improved opportunities. This study underscores the vital role of family financial education in fostering students' financial literacy, advancing parental socioeconomic status, and enhancing students' financial well-being.